Role of metastasectomy in the management of renal cell carcinoma - Mikhail, Mark; Chua, Kevin J.; Khizir, Labeeqa; Tabakin, Alexandra; Singer, Eric A. (Frontiers in Surgery, 2022)
Treatment of metastatic renal cell carcinoma (mRCC) has evolved with the development of a variety of systemic agents; however, these therapies alone rarely lead to a complete response. Complete consolidative surgery with surgical metastasectomy has been associated with improved survival outcomes in well-selected patients in previous reports. No randomized control trial exists to determine the effectiveness of metastasectomy. Therefore, reviewing observational studies is important to best determine which patients are most appropriate for metastasectomy for mRCC and if such treatment continues to be effective with the development of new systemic therapies such as immunotherapy. In this narrative review, we discuss the indications for metastasectomies, outcomes, factors associated with improved survival, and special considerations such as location of metastasis, number of metastases, synchronous metastases, and use of systemic therapy. Additionally, alternative treatment options and trials involving metastasectomy will be reviewed.